Exploring the Development of Pragmatic Assessments in Autism Spectrum Disorder: A Systematic Literature Review - Arum, Euis Reliyanti; Ekasari, Tetty; Widyana, Neny (Communication In Research And Publications, 2025)
Assessment for children with Autism Spectrum Disorder (ASD) has undergone significant development over the past decades. This study systematically reviews pragmatic assessment instruments used in clinical contexts for children with ASD. From an initial pool of 210 articles identified through academic database searches, a stepwise screening process (identification, abstract/title screening, and eligibility review) resulted in 21 eligible articles for full analysis. From these articles, 26 pragmatic assessment instruments were identified and systematically coded based on method of administration, target age group, assessed pragmatic features, and year of publication. The review reveals notable advancements, such as the adoption of video-based stimuli, inclusion of nonverbal elements, and use of multimodal approaches. However, several critical limitations remain, particularly the reliance on indirect parent or teacher reports (54%), which may overlook the dynamic aspects of social interaction. Most tools emphasize basic communicative functions (e.g., requesting, responding), with only 38% evaluating paralinguistic elements such as intonation and facial expressions. Moreover, approximately 80% of the instruments are designed for children under 12, leaving adolescents—who face increasingly complex pragmatic demands, including digital communication—underrepresented. Additionally, 88% of instruments were developed within Western cultural frameworks, raising concerns about cross-cultural validity in high-context cultures such as Indonesia. Two underserved groups also emerged: nonverbal children with ASD and adolescents primarily engaged in digital interaction. These findings suggest an urgent need for more inclusive, developmentally appropriate, and culturally responsive pragmatic assessment tools that can accommodate diverse communication styles and sociocultural contexts to ensure accurate and meaningful clinical evaluations.